Iklim Investasi dalam Penyelesaiannya Penerapan Omnibus Law - Wole, Bewa Dangu; Purwatiningsih, Annisa; Kamaluddin, Kamaluddin (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
There are five main factors that affect the entry of investors into a country, namely political stability, legal certainty, consistent policies, regulations, and taxes. This research is a literature study that summarizes some literature relevant to the theme. Data collection methods are literature studies that use books and literature, notes, journals and others as the main research objects. The purpose of this paper is to know the investment climate in Indonesia and the application of omnibus law as a solution, as well as to know the challenges of implementing omnibus law in Indonesia. The results showed that Indonesia was dubbed a hyperegulation country that reached 42,996 with details, central regulations as many as 8,414, ministerial regulations 14,453, non-ministry government agency regulations 4,164, and local regulations as many as 15,965. Too much will have an impact on the overlap and inconsistency of regulations between the center and the area causing vertical and horizontal conflicts. The government deregulates and debirokratization through omnibus law with two substances, namely the Omnibus Law Copyright Act which contains 11 clusters that combine 79 laws in which it concerns rules on employment, licensing alignment, investment requirements, to government administration. The challenge of implementing omnibus law is that Indonesia adheres to the civil law system while the concept of omnibus law adherents common law and still new. There is a public reaction between the pros and cons because the manufacturing process is not transparent and participatory, and omnibus law is not in accordance with the provisions of the establishment of laws and regulations. However, legally omnibus law is appropriate after the passing of Law No. 15 of 2019 concerning Changes to Law No. 12 of 2011.